Assertive Assertive Illocutionary Acts in The Main Character in Wish Movie - Ni Nyoman Camela Kesari Wahyunia Wulan; Ida Ayu Mela Tustiawati (Institut Agama Islam Negeri Palopo, 2024)
This study examined the illocutionary acts of assertive in the Wish movie using Searle’s speech act theory. The study explored how the protagonist, Asha, used assertive language to convey beliefs, provide information, and influence the narrative process. The study used a qualitative research design especially content analysis, to examine Asha’s dialogues and categories them into assertive acts such as asserting, reporting, informing, and arguing. The results showed that Asha frequently used assertive acts, indicating a strong tendency to reinforce beliefs and covey information. In addition, the analysis showed that reporting and telling actions were significant, indicating that Asha was a source of information in the film. This research contributes to understanding language use in cinematic contexts, emphasizing the importance of assertive communication in character development and storytelling. The study offers valuable insights into the pragmatic aspects of film dialogue and provides a foundation for further research in linguistics and media studies.